A case of globe rupture crossing calcified senile scleral plaque - Makoto Gozawa; Yusuke Orii; Yoshihiro Takamura; Masaru Inatani (American Journal of Ophthalmology Case Reports, 2024)
Purpose: To report a rare case of globe rupture with broken calcified senile scleral plaque (SSP). Observations: A 94-year-old male patient presented with left eye pain and severely decreased left vision immediately after the injury while farming. Examination of the left eye revealed edematous cornea, diffuse subconjunctival hemorrhage, total hyphema and iris prolapse. Preoperative computed tomography (CT) scan revealed calcified SSP in both eyes, and the calcified SSP was found to be broken during surgery. Although it was impossible to thread the broken calcified SSP, threading and suturing with long bites outside of the broken calcified SSP was effective for wound closure. Postoperatively, we were able to observe the broken calcified SSP and the wound closure using anterior segment optical coherence tomography (AS-OCT). Conclusions and importance: In a case of globe rupture with calcified SSP on preoperative CT, the possibility that the SSP has also ruptured should be considered. AS-OCT is also useful to observe the wound in a case of globe rupture with broken SSP during follow-up.